Growth retardation and cysteine deficiency in gamma-glutamyl transpeptidase-deficient mice. - Lieberman, M W (1996)
gamma-Glutamyl transpeptidase (GGT) is an ectoenzyme that catalyzes the first step in the cleavage of glutathione (GSH) and plays an essential role in the metabolism of GSH and GSH conjugates of carcinogens, toxins, and eicosanoids. To learn more about the role of GGT in metabolism in vivo, we used embryonic stem cell technology to generate GGT-deficient (GGTm1/GGTm1) mice. GGT-deficient mice appear normal at birth but grow slowly and by 6 weeks are about half the weight of wild-type mice. They are sexually immature, develop cataracts, and have coats with a gray cast. Most die between 10 and 18 weeks. Plasma and urine GSH levels in the GGTm1/GGTm1 mice are elevated 6-fold and 2500-fold, respectively, compared with wild-type mice. Tissue GSH levels are markedly reduced in eye, liver, and pancreas. Plasma cyst(e)ine levels in GGTm1/GGTm1 mice are reduced to approximately 20% of wild-type mice. Oral administration of N-acetylcysteine to GGTm1/GGTm1 mice results in normal growth rates and partially restores the normal agouti coat color. These findings demonstrate the importance of GGT and the gamma-glutamyl cycle in cysteine and GSH homeostasis.